2023
DOI: 10.3390/su15021497
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Drivers and Effects of International Science and Technology Cooperation in Xinjiang in the Context of the Belt and Road Initiative

Abstract: International science and technology (S&T) cooperation is one of the important ways to ensure the continuous development of a national innovation system. “One Belt One Road” advocates the concepts of common business, common construction, and sharing, and new countries and regions are constantly added. However, different countries/regions have different natural and socio-economic characteristics, so the main controlling factors affecting their international S&T cooperation may not be the same. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
0
0
0
Order By: Relevance
“…24 During the 2017 Belt and Road Forum, an official in Brazil's federal tax bureau indicated that Brazil was willing to actively participate in all aspects of the BRI. 25 A former Argentine Foreign Minister was similarly quoted as saying that the Initiative is 'a crucial multilateral integration project that goes beyond the traditional Silk Road to reach Latin America,' and that Argentina 'is willing to actively participate in the building of the Belt and Road'. 26 During Deputy Foreign Minister Qin Gang's visit to Suriname in 2017, that country's government also expressed its interest in participating in the Initiative.…”
Section: The Co-production Of the Bri In Latin Americamentioning
confidence: 99%
“…24 During the 2017 Belt and Road Forum, an official in Brazil's federal tax bureau indicated that Brazil was willing to actively participate in all aspects of the BRI. 25 A former Argentine Foreign Minister was similarly quoted as saying that the Initiative is 'a crucial multilateral integration project that goes beyond the traditional Silk Road to reach Latin America,' and that Argentina 'is willing to actively participate in the building of the Belt and Road'. 26 During Deputy Foreign Minister Qin Gang's visit to Suriname in 2017, that country's government also expressed its interest in participating in the Initiative.…”
Section: The Co-production Of the Bri In Latin Americamentioning
confidence: 99%